Juventude e sentidos do trabalho: estudos sobre ex-participantes do Projovem - Luiz Henrique Roberti (2010)
This dissertation aims to analyze which senses the young people involved in the participation of the Youth Inclusion National Program: Education, Qualification and Community Action (ProJovem) attach to Work, from their experiences and working and formation conditions. This study is inserted as an interface of the field of labor and education studies in the field of youth studies, considering changes in the workplace and its effects on social complexity, where constitutes the young people in process of transition to adulthood and insertion into the world of work. Our epistemological reference is historical materialism and dialectical conception of interpretation of reality, bases of analysis of Critical Theory. From which we introduce our object of study, the meanings of work for young, in the context of the changes of world of work derived from the processes of productive restructuring and capital accumulation, with consequences to other social spheres. We start from the position of centrality of work in human life as social wight, as well as its centrality in social relations of work and like basis of constitution of complexity of contemporary human society. This one, structured under capitalist relations of production at the stage of its organization and transnational development and informational technology. In the background, were developed analysis about the relevance of ProJovem in formation and senses that these young people have provided in work experience, locating the program in the context of public policy of the State, directed to the Brazilian youth. For this, we undertook an investigation about the implementation of the Program in Belo Horizonte, in its first phase, corresponding to the period from 2005 to 2007. Regarding the theoretical support, the study starts of sociological concept of youth, taking as central reference the sociological conceptions of José Machado Pais and, for analysis of the work category, those undertaken by Ricardo Antunes. Were used, in addition to other authors of reference included in the debates of the two fields of research, a qualitative methodology based on interviews with semi-structured screenplay. The interviews were developed with six young, men and women aged between twenty and twenty-eight years, at the time of the interviews, and ex-participants of ProJovem. Were also similarly interviewed five managers and coordinators of the program in Belo Horizonte. These interviews occurred from October 2009 to October 2010. Based on interviews and analysis of relevant literature, we concluded by identifying the importance and centrality of work in the lives of young people from the working classes, as well as the precariousness of their conditions of insertion and survival at work; which reflects the general difficulties in their lives, as youth in transition to an adult world. We also concluded that there are serious limitations in social programs for youth (and for the lower classes), like ProJovem, especially due the short range or social results of such programs, as well as because, essentially, constitute themselves as social control policies. However implemented by the state, increasingly restricted in terms of sovereignty, while assists in a frank instrumentation of an increasing power of the very dynamics of transnationalization of capital. Keywords: Labor. Youth. Meanings of Work. Produtive reestruturation.